Small mammals as hosts of vector-borne pathogens in the High Tatra Mountains region in Slovakia, Central Europe - Bronislava Víchová; Michal Stanko; Martina Miterpáková; Zuzana Hurníková; Yaroslav Syrota; Patrícia Schmer-Jakšová; Petronela Komorová; Lucia Vargová; Veronika Blažeková; Dana Zubriková; Klaudia Mária Švirlochová; Gabriela Chovancová (Current Research in Parasitology and Vector-Borne Diseases)
Rodents and insectivores are significant reservoirs of many zoonotic pathogens, contributing to the transmission of diseases affecting human and animal health. This study investigated the prevalence and diversity of vector-borne pathogens in small mammals within the High Tatras region of Slovakia, an area with substantial recreational activity and protected zones. A total of 156 small mammals, comprising ten species, were screened for pathogens such as Bartonella spp., Borrelia spp., Anaplasma phagocytophilum, and Babesia spp. The prevalence of vector-borne pathogens in the studied animals reached 74.35%, with Bartonella spp. being the most common, identified in 57.7% of the animals, particularly in Apodemus flavicollis and Clethrionomys glareolus. Borrelia burgdorferi (sensu lato) was detected in 11.5% of the rodents, with Borrelia afzelii identified as the predominant species. Babesia microti was found in A. flavicollis and Mus musculus, with a total prevalence of 3.2%. The lowest was the prevalence of A. phagocytophilum reaching 1.9%. This study provides evidence of the significant role of rodents as reservoirs of vector-borne pathogens in protected areas of the High Tatras region and Tatra National Park.